Factors influencing consumer behaviour - J. Stávková; L. Stejskal; Z. Toufarová (Agricultural Economics (AGRICECON), 2008)
The main aim of the article is to understand the influence of factors biasing purchase decisions connected with measurement of consumers' involvement. Consumption expenditures are purposefully subdivided according to the classification made by the Statistical Office of the European Communities. The performed survey showed that the most important factors biasing purchases of all commodity groups are products' characteristics and the perceived quality. Together with these goes the factor price, nevertheless for example for the commodity group health price did not appear in the scale of the perceived importance at all. Factor necessity of need proved to be significant for decision making about the purchase of all commodities with the exception of alcoholic drinks and tobacco and recreation. Former experience compared to that is not crucial for clothing and footwear and housing equipment and contents. For alcoholic drinks and tobacco, there has notably approved also the factor brand. These analyses enable disclosure of rules of consumer decision making and thereby definition which factors for individual commodities should be targeted by the help of the marketing doyens or where the gradual changes should be achieved.